Discovering Iqbal's educational vision: wisdom for today's world - Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (Mission Soft Foundation, 2023)
From time immemorial to the modern world in which we live today, man and education are two entities that are inseparable. Prior to modern civilization and modernity, there appeared in many parts of the world, prophets, philosophers, sages and great men of wisdom who taught and guided humanity to the path of virtue and righteousness. As the world progressed and entered into its modern phase, things and lifestyles changed. Teaching and education were institutionalized. Along with that came a structured educational system all over the world. Since then, parents and teachers have the vital role in educating the young minds who are under their care, into responsible human beings. During the olden days, at the very core of all educational systems in the world, instilling values and bringing out the humanness from the soul of every learner was a crucial role that weighed heavy on the shoulders of teachers. All these lofty idealisms of what should be a good education changed with the coming age of the Industrial Revolution, modernity, globalization and the latest, AI.